Epic Cruelty: On Post-Pandemic Performance. (May 2021) - Mitchell, Rick
Abstract : As today's catastrophic Covid-19 pandemic exacerbates ongoing crises, including systemic racism, rising ethno-nationalism, and fossil-fuelled climate change, the neoliberal world that we inhabit is becoming increasingly hostile, particularly for the most vulnerable. Even in the United States, as armed white-supremacist, pro-Trump forces face off against protesters seeking justice for African Americans, the hostility is increasingly palpable, and often frightening. Yet as millions of Black Lives Matter protesters demonstrated after the brutal police killing of George Floyd, the current, intersecting crises – worsened by Trump's criminalization of anti-racism protesters and his dismissal of science – demand a serious, engaged, response from activists as well as artists. The title of this article is meant to evoke not only the state of the unusually cruel moment through which we are living, but also the very different approaches to performance of both Brecht and Artaud, whose ideas, along with those of others – including Benjamin, Butler, Latour, Mbembe, and Césaire – inform the radical, open-ended, post-pandemic theatre practice proposed in this essay. A critically acclaimed dramatist as well as Professor of English and Playwriting at California State University, Northridge, Mitchell's published volumes of plays include Disaster Capitalism; or Money Can't Buy You Love: Three Plays ; Brecht in L.A. ; and Ventriloquist: Two Plays and Ventriloquial Miscellany. He is the editor of Experimental O'Neill, and is currently at work on a series of post-pandemic plays.